2023
DOI: 10.3390/polym15081899
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of Corn Starch Films for Sustainable Food Packaging by Optimizing Enzymatic Hydrolysis

Abstract: The objective of this study was to investigate the effects of enzymatic hydrolysis using α-amylase from Bacillus amyloliquefaciens on the mechanical properties of starch-based films. The process parameters of enzymatic hydrolysis and the degree of hydrolysis (DH) were optimized using a Box–Behnken design (BBD) and response surface methodology (RSM). The mechanical properties of the resulting hydrolyzed corn starch films (tensile strain at break, tensile stress at break, and Young’s modulus) were evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…In previous studies, the dynamic-mechanical properties of bioplastics derived from different sources have been investigated. For example, a previous study reported the E 1B values for bioplastics made from corn starch to be around 0.5-0.7 Pa [52], which is comparable to our findings for taro (0.69 ± 0.05 Pa). However, our study demonstrated that yucca-based bioplastics have a higher E 1B value of 1.46 ± 0.08 Pa, indicating superior mechanical properties compared to corn-starch-based bioplastics.…”
Section: Systemsupporting
confidence: 91%
“…In previous studies, the dynamic-mechanical properties of bioplastics derived from different sources have been investigated. For example, a previous study reported the E 1B values for bioplastics made from corn starch to be around 0.5-0.7 Pa [52], which is comparable to our findings for taro (0.69 ± 0.05 Pa). However, our study demonstrated that yucca-based bioplastics have a higher E 1B value of 1.46 ± 0.08 Pa, indicating superior mechanical properties compared to corn-starch-based bioplastics.…”
Section: Systemsupporting
confidence: 91%
“…In this figure, it is possible to observe that the typical dynamic mechanical behavior of storage modulus for starch can be seen under a temperature range, and it is evident that the stiffness decreases as a function of the temperature. In addition, it is regarded as a material ability to store applied energy for future purposes, which provides information about the stiffness of the material under cyclic stress [ 46 , 48 , 49 , 50 , 51 ]. Usually, the addition of a reinforcer material in a polymer matrix improves its mechanical properties because the applied stress can be transferred to the reinforcement, which helps the polymer matrix during the mechanical stress and associates the filler dispersion and compatibility between the materials to be mixed.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the properties of thermoplastic starch films, the starch can be modified prior to film preparation by combining it with other biodegradable materials or reinforcing it with active or natural nanoparticles. The enzymatic hydrolysis using α-amylase from Bacillus amyloliquefaciens can be used successfully to improve corn starch-based film's mechanical properties, such as greater elasticity, strength, and stiffness [6]. Adding various natural extracts improves the mechanical properties of the starch-based films, i.e., Thymus vulgaris essential oils (TEOs) combined with ethanolic extract of propolis (EEP) increases the elongation at break up to 13.5% [7].…”
Section: Introductionmentioning
confidence: 99%